The Mechanism and Function of Glia in Parkinson's Disease - Zhang, Xinguo; Zhang, Ruiqi; Nisa Awan, Maher Un; Bai, Jie (Frontiers in Cellular Neuroscience, 2022)
Parkinson's disease (PD) is a neurodegenerative disease that primarily affects the elderly people. The mechanism of onset and progression of PD is unknown. Currently there are no effective treatment strategies for PD. PD is thought the loss of midbrain dopaminergic neurons, but it has recently been discovered that glia also affects brain tissue homeostasis, defense, and repair. The neurodegenerative process is linked to both a loss of glial supportive-defensive functions and a toxic gain of glial functions. In this article we reviewed the role of microglia, astrocytes, and oligodendrocytes in the development of Parkinson's disease, as well as the potential use of glia-related medications in PD treatment.